Mechanical Thrombectomy as the Treatment of Choice for Ischemic Stroke Large Vessel Acocclusion - Pinto Desti Ramadhoni (Arkus, 2018)
Despite major advances in stroke management in the last 2 decades, stroke is still the leading cause of disability and death worldwide. Current ischemic stroke therapy aims to improve long-term outcomes in stroke patients. For this purpose, early recanalization is the only promising therapy for acute ischemic stroke. The main goal of reperfusion therapy in acute ischemic stroke is to immediately improve blood flow (recanalization) in areas of the brain that are ischemic and have not undergone infarction. The long-term goal is to increase outcomes by reducing disability and death from stroke. The most important factor in the success of reperfusion therapy in acute ischemic stroke is therapy as early as possible. However, selection of suitable candidates for reperfusion therapy requires neurologic evaluation and neuroimaging studies.